Multiple cosmogenic nuclides to decipher the complex exposure history of the East Antarctic Ice Sheet - BORRACCINI, GIANLUCA (Pisa University, 2023)
The aim of this thesis is the Surface Exposure age Dating (SED) of samples collected in deglaciated areas of Victoria Land during several expeditions of the Italian National Antarctic Research Program (PNRA 1997-98, 2004-05, 2011-13) by the supervisors of this thesis (Proff. C. Baroni and M.C. Salvatore, University of Pisa). In particular, the samples were collected to contribute to the reconstruction of the Pleistocene history of the Antarctic glacial system and the subsequent stages of the retreat of the Antarctic icesheets. The analyzed samples were taken from erratic boulders of granitoid rocks, deposited during repeated Pleistocene advances of the Antarctic glacial system on Ross Island, a volcanic island located in the West Ross Sea at the edge of the East Antarctic Ice-Sheet. In fact, during the Last Glacial Maximum (MIS 2) the grounding line of the Ross Platform advanced northward to the edge of the continental shelf, causing a relevant increase in the glaciers’ thickness in coastal areas. The SED method relies on the calculation of the concentration of cosmogenic nuclides that have formed on a surface since it was exposed to cosmic radiation. Secondary cosmic rays (mainly neutrons) interact by spallation reaction with atoms contained in target minerals on the surface, accumulating the cosmogenic isotopes. Through laboratory procedures, from the target minerals are extracted the nuclides to analyze. With an AMS is then calculated the ratio between the concentration of the cosmogenic isotope of interest and that of the corresponding stable isotope, from which the concentration of the single cosmogenic nuclide is obtained. Thanks to the known production rate and half-life of the isotope, and to other factors to consider, the surface exposure age is calculated from the concentration. It was possible to prepare and process samples for this kind of analysis thanks to the work carried out in specialized universities and research centers, under the guidance of experts in the field. At the Department of Earth ...